Synthesis, structure, and characteristic of Zn(II) and Cd(II) coordination compounds with 3-methoxybenzene acid hydrazide and their biological activity - Roman, Ljudmyla; Chundak, Stepan (Publishing House of Lviv Polytechnic National University, 2014)
Zinc(II) and cadmium(II) coordination compounds with 3-methoxybenzene acid hydrazide have been received from the hot ethanol or hydra-ethanol solutions in slightly acidic environment. Composition of the synthesized complexes is suggested on the basis of chemical analysis and the study of electrical conductivity of their solutions. The structure of the coordination compounds is established with the help of 1Н NMR and IR-spectroscopy and thermogravimetry as well as quantum-chemical calculations in the approximation of PM3. Two molecules of organic ligand in amidohydrazonic form take part in the building of strong Zn(II) and Cd(II) coordination compounds with 3-methoxybenzene acid hydrazide. In this process their coordination with the central metal ion proceeds chelate-bidentately with the formation of С=О→Ме and Ме←NH2 bonds. Octahedral surrounding of the central atom is added with anions of (NO3 – or Cl–, respectively) acidic remains or with water molecule. The synthesized coordination compounds show antibacterial properties against microorganisms of the following strains: Acinetobacter baumanni, Sarcina flava, Pseudomonas aeruginosa, Streptococcus pneumoniae, and Bacillus subtilis as well as bacteriostatic properties against Escherichia coli, Salmonella typhimurium, Klebsiella pneumoniae, MRSA, Enterobacter cloaceae, and Klebsiella oxytoca. З використанням гарячих етанoльних або водно-етанольних розчинів у слабо кислому середовищі (рН = 4,0–5,0) отримано координаційні сполуки Zn(II) і Cd(II) з гідразидом 3-метоксибензенової кислоти. На основі хімічного аналізу та вивчення електропровідності розчинів запропоновано склад синтезованих комплексів. За допомогою методів 1Н ЯМР та ІЧ-спектроскопії, термогравіметрії та квантово-хімічних розрахунків у наближенні РМ3 встановлено будову координаційних сполук. Показано, що в утворенні міцних координаційних сполук Zn(II) і Cd(II) з гідразидом 3-метоксибензенової кислоти беруть участь дві молекули органічного ліганду у амідогідразоновій формі. Встановлено, що координація сполук до центрального йону металу проходить хелатно бідентатно з утворенням зв’язків С=О→Ме і Ме←NH2 з доповненням октаедричного оточення центрального атому аніонами кислотних залишків (NO3 - чи Cl- відповідно) або молекулами води. Синтезовані координаційні сполуки проявляють бактерицидні властивості по відношенню до мікроорганізмів штаму Acinetobacter baumanni, Sarcina flava, Pseudomonas aeruginosa, Streptococcus pneumoniae, Bacillus subtilis, а також бактеріостатичні – по відношенню до Escherichia coli, Salmonella typhimurium, Klebsiella pneumoniae, MRSA, Enterobacter cloaceae, Klebsiella oxytoca.
Синтез, будова, властивості координаційних сполук Zn(II) І Cd(II) з гідразидом 3-метоксибензенової кислоти та їх біологічна активність
Keywords: 3-methoxybenzene acid hydrazide; zinc coordination compounds; cadmium coordination compounds; structure of synthesized substances; biological activity; гідразид 3-метоксибензенової кислоти; координаційні сполуки цинку; координаційні сполуки кадмію; будова синтезованих речовин; біологічна активність